2016
DOI: 10.1007/s11255-016-1473-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of multiple fluid status assessment methods in patients on chronic hemodialysis

Abstract: The BLS is a useful and easily performed technique that has recently become available for accurate evaluation of dry weight and fluid status in patients with end-stage renal disease undergoing chronic HD. This method might help recognize asymptomatic lung congestion in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 51 publications
4
31
1
Order By: Relevance
“…In order to evaluate overall body fluid status, blood pressure, body weight, and edema severity are often used as indicators of fluid status. In order to achieve a more precise estimation, these measurements have been combined with different techniques, such as relative blood volume monitoring, pulmonary ultrasonography, measurement of the inferior vena cava diameter, and bioimpedance . These methods are used to various degrees in the clinical setting, but no single method has had a proven substantial effect on survival.…”
Section: Introductionmentioning
confidence: 99%
“…In order to evaluate overall body fluid status, blood pressure, body weight, and edema severity are often used as indicators of fluid status. In order to achieve a more precise estimation, these measurements have been combined with different techniques, such as relative blood volume monitoring, pulmonary ultrasonography, measurement of the inferior vena cava diameter, and bioimpedance . These methods are used to various degrees in the clinical setting, but no single method has had a proven substantial effect on survival.…”
Section: Introductionmentioning
confidence: 99%
“…This finding may be largely dependent on the time lag in plasma refilling. Alexiadis et al reported that the number of B-lines has better discriminative power for predicting over-and underhydration, as determined by the IVC dimensions [2]. Mallamaci et al suggested that the detection of extracellular water in the lung compartment constitutes a reliable tool for the prognosis of overhydration and is thus amenable to intervention [19].…”
Section: Discussionmentioning
confidence: 99%
“…Lung ultrasound has recently been shown to be a useful, noninvasive technique for the assessment of extravascular lung water [2]. The most commonly observed finding was a comet tail artifact fanning out from the lung-wall interface and spreading upwards to the edge of the screen, previously named a "B-line" [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients in whom dry weight was reached according to this operational definition, using long dialysis hours in combination with meticulous sodium restriction have lower extracellular volume and better survival [41][42][43]. In general, dry weight is assumed to coincide with normalization of ECV, although substantial differences may be observed between clinical judgment and information obtained by additional technologies [44,45]. Interestingly, in a cohort study in 639 PD patients, 28% of the population was fluid overload, defined as OH: ECV ratio > 7%, in combination with a normal or low blood pressure [1].…”
Section: The Dry Weight Conceptmentioning
confidence: 99%